Sidney Sheldon's reckless - Bagshawe, Tilly (William Morrow, an imprint of HarperCollinsPublishers, 2015)
Forced to confront her greatest nightmare in the face of a tragedy, Tracy Whitney returns to the world of her past to confront a terror threat from a group of global hackers intent on the collapse of capitalism.